Nutritional Status of Under Five Year Children Residing in Selected Wards of Barahachhetra Municipality, Sunsari, Nepal: a Cross-sectional Study - Sigdel, Rambha; Adhikari, Dewa; Badhu, Angur; Shah, Tara (Journal of BP Koirala Institute of Health Sciences, 2022)
Background: The nutrition of under five children reflects a country’s health status. We aimed to assess the nutritional status of the under five year children of selected wards of Barahachhetra municipality, Sunsari.Methods: In this cross-sectional study, we enrolled 167 under five year children in ward no. 4 and 5 of Barahachhetra municipality. Height/ length, mid- upper arm circumference (MUAC), weight and clinical signs of malnutrition were noted. The relevant information regarding the predictors of malnutrition was obtained from parents/ caregiver.Results: Nearly half (47.9%) of the children were in the age group 25-59 months with almost equal gender distribution. About one-tenth of children (11.3%) had MUAC less than 12.5 cm, 20.4% of children were wasted, 47.2% were stunted and more than a quarter (29.6%) were underweight. The MUAC was significantly associated with per capita income (p = 0.01). Wasting was significantly associated with the age of the children (p = 0.005) and occupation of their father (p = 0.002). Underweight was significantly associated with their age (p = 0.007), ethnicity (p = 0.03), parents’ education (mother: p = 0.02, father: p = 0.002), parents’ age (mother: p = 0.04, father: p = 0.02) and fathers’ occupation.Conclusion: Substantial number of under five year children were malnourished. One-fourth of the children were wasted, nearly half were stunted, and more than a quarter of the children were underweight. Malnutrition (as per MUAC) and stunting were higher among younger children (6-24 months) whereas wasting and underweight were higher among older children (25-59 months).